2022
DOI: 10.1186/s12906-022-03676-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and anti-trichomunas characteristics of local landraces of Lawsonia inermis L.

Abstract: Background Henna (Lawsonia inermis) with anti-bacterial properties has been widely used in traditional medicine especially Persian medicine. Henna oil is suggested for diseases of infectious origin, such as cervical ulcers. Group B Streptococcus agalactiae, Pseudomonas aeruginosa and, Trichomonas vaginalis are involved in the infection of women especially cervicitis. Henna grows in dry and tropical regions. The main important landraces of henna landraces are cultivated in Kerman, Sistan and Bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This can be confirmed by examining the skin pH between the toes, which is significantly higher in diabetics than in the general population [56]. It should be noted that henna has some antimicrobial properties [57]. However, the authors indicate that the most important preventive action for diabetic patients is to protect against maceration and skin damage in the interdigital area.…”
Section: Other Plant Raw Materialsmentioning
confidence: 86%
“…This can be confirmed by examining the skin pH between the toes, which is significantly higher in diabetics than in the general population [56]. It should be noted that henna has some antimicrobial properties [57]. However, the authors indicate that the most important preventive action for diabetic patients is to protect against maceration and skin damage in the interdigital area.…”
Section: Other Plant Raw Materialsmentioning
confidence: 86%
“…Henna extracts and oils have traditionally been used to treat various infectious disorders, including those caused by Pseudomonas aeruginosa , group B Streptococcus agalactiae , and Trichomonas vaginalis . In the wake of the emergence of antibiotic-resistant bacteria, the use of novel strategies and alternative methods might assist in mitigating future resistance (Bafghi et al, 2022 ). Research by Mickymaray et al ( 2016 ) has demonstrated that henna exhibits several environmentally beneficial effects, encompassing antibacterial, antifungal, and antiparasitic properties.…”
Section: Microbial and Insect Biocidesmentioning
confidence: 99%
“…The application of these plants is also closely linked to the lives of Moroccans for cultural, folkloric, prophetic or religious reasons [8,9]. L. inermis, commonly referred to as Henna in Arab countries, is the most popular and widespread in tropical areas [10]. L. inermis belongs to the family Lythraceae, whose leaves play a particularly significant component.…”
Section: Introductionmentioning
confidence: 99%